Osteoporosis Management in a Real Clinical Setting: Heterogeneity in Intervention Approach and Discrepancy in Treatment Rates when Compared with the NOGG and NOF Guidelines - Kyriakos, G.; Vidal-Casariesgo, A.; Quiles-Sánchez, L. V.; Urosa-Maggi, J. A.; Calleja-Fernández, A.; Hernández-Moreno, A.; Ballesteros-Pomar, M. D.; Cano-Rodriguez, I. (Experimental and Clinical Endocrinology & Diabetes, 2016)
Objective: The National Osteoporosis Guideline Group (NOGG) proposes intervention thresholds that vary by age. Instead, the National Osteoporosis Foundation (NOF) proposes a fixed threshold for decision. The aim of the present study was to compare the actual therapeutic decisions taken in a routine clinical practice setting with those recommended by the NOF and NOGG guidelines.Material and methods: A cross-sectional study was conducted in individuals referred to a densitometric unit who were not receiving antiresorptive therapy. The absolute risk of major and hip fracture was calculated using the British formula provided by the FRAX® tool. NOGG and NOF guidelines’ therapeutic intervention thresholds were used. Agreement was calculated using Cohen’s kappa.Results: A total of 640 individuals were included, of which 95% were women, with a median age of 59.4 (IQR=14) years. 31.7% of subjects who were analyzed received treatment for osteoporosis. The type of treatment that was mainly prescribed (71.9%) consisted of bisphosphonates. When applying the NOGG criteria, treatment was recommended in 22.7% of cases; this percentage increased to 42.2% with the NOF guidelines. According to both guidelines, 20.4% of patients would not have received treatment. The concordance, expressed as the kappa index, was low; 0.25 (CI 95% 0.17–0.34) and 0.49 (CI 95% 0.42–0.55), with the NOGG and NOF, respectively.Conclusions: Important heterogeneity exists in the treatment of osteoporosis in real practice. The choice of guideline has a major impact on the proportion and selection of individuals recommended for treatment and, subsequently, on treatment-related expenditures.
Keywords: osteoporosis; antiresorptive agents; FRAX; NOGG; NOF